Rede Cegonha and its impacts on births in a region of northeastern Brazil (Research, Society and Development, 2021)
Objective: to analyze the impact of the Rede Cegonha Strategy in Alagoas on births from 2011 to 2018. Method: ecological study, time series, with secondary data from DATASUS. The data were processed using the Statistical Package for the Social Sciences software. Variables were the mortality coefficient between the years 2011 to 2018, the relationship between the total number of deaths from preventable causes, through multiple regression (p